1997
DOI: 10.1002/(sici)1097-0339(199708)17:2<153::aid-dc13>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Direct intrauterine sampling: The IUMC endometrial sampler

Abstract: Endometrial cytology has been studied for more than 25 years, and a variety of cytologic devices have been developed for direct sampling of the endometrium. The quality of endometrial samples procured by various devices is markedly different and greatly affects the diagnostic accuracy. A new endometrial sampling device, the IUMC Endometrial Sampler, was developed at the Indiana University Medical Center and approved by the Food and Drug Administration for general medical use. This device is intended for the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…The Tao Brush was introduced in 1993 and approved by the Food and Drug Administration for general medical use (Tao 1997) (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…The Tao Brush was introduced in 1993 and approved by the Food and Drug Administration for general medical use (Tao 1997) (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…During the recent decades, a variety of endometrial sampling devices have been used, with distinct advantages and disadvantages. 6 It has been proved that endometrial sampling is a well-tolerated, inexpensive procedure for obtaining information about the endometrium. 6,11 Previous studies have shown that the sensitivity and the specificity of various endometrial devices range from 50 to 100% and from 85 to 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…6 It has been proved that endometrial sampling is a well-tolerated, inexpensive procedure for obtaining information about the endometrium. 6,11 Previous studies have shown that the sensitivity and the specificity of various endometrial devices range from 50 to 100% and from 85 to 100%, respectively. 10,[12][13][14] However, cytological investigation of the endometrial cavity is not accepted worldwide as a method for the mass screening of the female population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also provides information about the endometrial phase, and has the potential to be used as a screening device for patients at high risk. [1][2][3][4] We planned a study to determine the accuracy of endometrial brush cytology processed by the ThinPrep method. The preliminary results are presented here.Endometrial samples were collected from 35 consecutive hysterectomy specimens by using the Tao brush.…”
mentioning
confidence: 99%